การศึกษาการนำนโยบายสาธารณะด้านเทคโนโลยีสารสนเทศและการสื่อสารไปปฏิบัติ สำหรับการให้บริการเกมออนไลน์และอินเทอร์เน็ต: The Implementation of Information and Communication Technology Policy for Online Game and Internet - Asawaveeradet, Chatchaya (Asian Health, Science and Technology Reports, 2010)
The study on “Implementation of Information and Communication Technology Policy for Online Game and Internet” was the qualitative research. There were 2 objectives: (1) to study implementation’s results of enterprise control laws and (2) to study factors affecting success or failure of implementation of enterprise control laws. The snowball and purposive sampling technique were employed. The two groups of key informants comprised of ten of enterprise owners and four of law implementation stakeholders. The research tool was in-depth interview form and content analysis was employed. The results were that for the implementation laws on controlling online game and internet services. The majority of online game operators had legally registered video operators, paid online-program license fee, recorded play hours, and did not sell alcohols which were legally. However, some of game online operators installed unlicensed programs and did not have ID card inspection and time control. So they did not complied with provisions of laws. For the factors affecting success or failure of law implementation showed that the principle causes were the policy standard factors due to law makers have no appropriate understanding of environment and online game characteristics. It also caused the communication and law enforcement factors to be unclear. The consequence was insufficient resources resulting in an inefficient function factor.